Targeted Therapies and other Agents as First-Line Maintenance and Beyond: Particular Benefit in Pulmonary Adenocarcinoma Patients - Petrelli, F.; Borgonovo, K.; Cabiddu, M.; Ghilardi, M.; Barni, S. (Current Medicinal Chemistry, 2011)
As of today, advanced non-small cell lung cancer is still an incurable disease. However, recent researches on the biology of adenocarcinoma have led to considerable progress in the treatment of this subgroup of patients. The administration of bevacizumab and pemetrexed as first-line therapy, erlotinib in the maintenance phase and erlotinib again combined with vandetanib as second-line therapy, gives patients with lung adenocarcinoma new hope. In particular, in metastatic adenocarcinoma with an EML4-ALK fusion oncogene, crizotinib (a selective, ATP-competitive, small molecule, orally bioavailable inhibitor of the ALK and MET/HGF receptor tyrosine kinases), led to a response rate of 64%, which is similar to the results achieved in chronic myeloid leukemia and GIST with imatinib. Overall, the application of all available active therapies during the natural history of adenocarcinoma may lead to a survival benefit that was unimaginable only a few years ago. This article reviews the main studies on molecular targeted therapies in various lines of treatment of advanced lung adenocarcinoma.
Keywords: adenocarcinoma